Konsep Manajemen Perubahan Dalam Meningkatkan Disiplin Kerja Oraganisasi - Imam Solehuddin; Nur Ahmadi Bi Rahmani (Jurnal Ekonomi dan Bisnis Digital, 2023)
Change management is a systematic approach designed to manage change in an organization. This involves the process of planning, implementing and monitoring change in order to manage its impact on individuals and the organization as a whole. Change management involves certain steps to ensure that changes are accepted and implemented effectively. The purpose of this research is to find out what things you need to know about change management. The type of research used is library research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The results of this research conclude several things such as the definition of change management, the goals and benefits of change management, types of change and change management approaches.